2022
DOI: 10.3389/fenvs.2022.927588
|View full text |Cite
|
Sign up to set email alerts
|

Online monitoring and sampling analysis of siltation in the middle route of the south-to-north water diversion project

Abstract: The middle route project (MRP) of the South to North Water Diversion Project is a significant infrastructure and alleviating water scarcity in Northern China. MRP suffered from untraditional siltation problems. Obvious siltation occurred in the regulating reservoir at the end of the channel and some locations with weak hydrodynamic conditions in the channel when the mineral siltation concentration in the flow is very low. To study the characteristics of the siltation and the siltation time period, an IoT based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The reviewed literature has also extensively covered the use of sensors and their performance in real-world settings. Researchers have utilized varying levels of experimentation, validation, and reliability testing to evaluate the accuracy and reliability of sensor readings [64], [134], [135], [138], [140]. In this regard, Wong et al [141] conducted a calibration and validation study on turbidity and ultrasonic water level sensors.…”
Section: ) Sensors and Sensing Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The reviewed literature has also extensively covered the use of sensors and their performance in real-world settings. Researchers have utilized varying levels of experimentation, validation, and reliability testing to evaluate the accuracy and reliability of sensor readings [64], [134], [135], [138], [140]. In this regard, Wong et al [141] conducted a calibration and validation study on turbidity and ultrasonic water level sensors.…”
Section: ) Sensors and Sensing Technologiesmentioning
confidence: 99%
“…For example, Ahmed et al [139] compared 16 different ML algorithms for potability prediction and found that a onedimensional convolutional neural network (CNN) performed significantly better than other classifiers. However, while ML algorithms are gaining popularity, traditional statistical methods remain prevalent in water quality monitoring research [135], [148]. For instance, Al-Khashab et al [143] used MATLAB to analyze and display the collected data, while Zakaria et al [149] utilized statistical methods such as coefficient of variation, standard deviation, and mean for data analysis.…”
Section: ) Sensors Data Analytics and Visualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Te development of fsh community function is lagging behind, and the top-down efects of the ecosystem is weak. Terefore, it is very necessary to explore fsh diversity, biology, and population dynamics for better conservation in this project [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…As it travels through North China, the main canal crosses two climate zones, the subtropical monsoon humid climate zone and the temperate monsoon climate zone, with an average annual precipitation of 542-1173 mm and a multi-year air temperature of 14.6-21.2 • C. The project officially began supplying water in December 2014, providing water resources for domestic, industrial, and agricultural water consumption for four provinces or municipalities along the main canal, including Henan Province, Hebei Province, Tianjin Municipality, and Beijing Municipality. By the end of 2022, the MSNWDP had supplied over 60 billion m 3 of water to more than 20 cities, directly benefiting more than 70 million people [1,2].…”
Section: Introductionmentioning
confidence: 99%